Dietary Intake, Nutritional Status, and Quality of Life in Patients with Thalassemia Major - Steven Yulius Usman; Salvabilla Azheema Rahmat; Vetinly Vetinly; Felicia Kurniawan (Althea Medical Journal, 2022)
Background: Impaired growth and inadequacy of dietary intake in thalassemia patients may affect the quality of life. This study aimed to determine and examine the relationship between dietary intake, nutritional status, and quality of life in in patients with thalassemia major.Methods: This study was a cross-sectional descriptive study conducted from February to October 2020. Twelve respondents who were registered at the Yayasan Thalassemia Indonesia and the blood transfusion unit at Fatmawati Hospital participated. This study conducted a physical examination and distributed food record questionnaires and WHOQOL-BREF. Data analysis was performed using Nutrisurvey 2007 and Fisher’s exact test.Results: The majority of the respondent were male (58.3%), categorized in the age group 5–18 years (58.3%), had normal nutritional status (50%) and quality of life. Interestingly, the respondents had an excess intake of protein and fats, while the intake of energy and carbohydrates was normal. Respondents had less intakes of all micronutrients. Conclusion: The majority of respondents have normal nutritional status and quality of life but have a low intake of micronutrients. Both patients and parents need to be further educated on dietary intake to meet their nutritional needs